2018
DOI: 10.1186/s12913-018-3486-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an educational intervention to improve antibiotic dispensing practices for acute respiratory illness among drug sellers in pharmacies, a pilot study in Bangladesh

Abstract: BackgroundInappropriate dispensing of antibiotics for acute respiratory illness (ARI) is common among drug sellers in Bangladesh. In this study, we evaluated the impact of an educational intervention to promote guidelines for better ARI management among drug sellers.MethodsFrom June 2012 to December 2013, we conducted baseline and post-intervention surveys on dispensing practices in 100 pharmacies within Dhaka city. In these surveys, drug sellers participated in 6 standardized role-playing scenarios led by stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 36 publications
1
40
1
Order By: Relevance
“…The alternative to restricting access to antibiotics through drug shop, is to improve their practice. This has been tried in Bangladesh, although drug shop sellers’ habits have proved difficult to shift [33]. Internationally, there is limited evidence so far about interventions to improve drug shop practice [15].…”
Section: Discussionmentioning
confidence: 99%
“…The alternative to restricting access to antibiotics through drug shop, is to improve their practice. This has been tried in Bangladesh, although drug shop sellers’ habits have proved difficult to shift [33]. Internationally, there is limited evidence so far about interventions to improve drug shop practice [15].…”
Section: Discussionmentioning
confidence: 99%
“…Health sector (combined by 'OR') (b) Geographic location (combined by 'OR') (c) and/or its indiscriminate use [17]. Studies reveal two or more antimicrobials to be commonly prescribed at a time in Bangladesh [14,15,18,19,20,22,30,31], and more antimicrobials to be prescribed in hospital settings compared to community settings [21].…”
Section: Amr (Combined By 'Or') (A)mentioning
confidence: 99%
“…7 Availability of antibiotics from pharmacies without authorized prescription and overuse or misuse of antibiotics such as self-medication practice, non-adherence to the prescription, inappropriate prescribing, and lack of antibiotic susceptibility testing can play a vital role in the evolvement of antibiotic resistance. [8][9][10] Moreover, the uncontrolled antibiotics applications in animal husbandry as therapeutic, prophylactic, and growth enhancers can contribute to the emergence of resistant bacteria that enter humans through the food chain. 11 A study indicated that South East Asia is at the highest risk of developing and spreading antibiotic resistance, and it suggested One Health approach to address this problem.…”
Section: Introductionmentioning
confidence: 99%